Analysis of Financial Distress in the Infrastructure Sector through the Altman Z-Score Approach - Brigita Puji Lestari; Nurshafikah Shaffie; Agnes Sulistiyoningsih (Journal of Accounting and Auditing, 2026)
Purpose – This study aims to obtain empirical evidence regarding the effect of Operating Cash Flow and Solvency on Financial Distress. Design/methodology/approach – This   study   uses   quantitative research.  It  utilizes  secondary  data.  The  population  is  71  infrastructure sector companies listed on the Indonesia Stock Exchange between 2022 and 2024. The  sample  is 37 infrastructure sector companies listed on the Indonesia Stock Exchange between 2022 and 2024.  The total number of observations in this study is 111. The analysis technique used to test the hypotheses is multiple regression analysis using Eviews9 software Findings – The results of this study indicate that the operating cash flow variable has a negative and significant effect on financial distress. The solvency variable has  a  negative and significant effect  on  financial distress. Research limitations/implications – This study contributes to financial distress literature by providing empirical evidence from the infrastructure sector and highlights the importance of cash flow management and debt control in maintaining financial stability. JEL : M4